Synchrony of love: a fNIRS study on emotional responses of men and women in romantic relationships - Valerie, Teo Huanqi (2017)
There has been extensive interest surrounding emotional behavior in different genders, and its implications over the years. This paper intends to extend the findings in existing literature and explore gender differences in emotional responses of romantic partners in heterosexual relationships, when placed under different emotional conditions. Additionally, we also discussed the role of emotional attunement in romantic attachment. To elicit positive and negative emotions, each couple is placed in the lab and exposed to the same video stimulus at the same time, in the presence of each other, and used NIRS to measure their hemodynamic responses. With functional neuroimaging techniques, we can gain a better understanding of the neurological mechanisms underpinning these processes. Results showed that there were differences in brain activity in men and women in both positive and negative conditions. Specifically, positive emotions elicited greater activity in men than women in inferior frontal gyrus and orbitofrontal cortex. In contrast, negative emotions stimulated greater activity in women than men in inferior frontal gyrus, dorsal lateral and medial frontal cortices. This reflects that men and women may have different emotional response tendencies when exposed to different emotion valences. Also, specific brain regions activations highlight that there are gender differences in terms of the extent of effort for certain emotional processes. Our findings in this study are important because they provide us with possible insights on romantic relationship dynamics.